An ex ante economic and policy analysis of research on genetic resistance to livestock disease: Trypanosomiasis in Africa - Falconi, C.A.; Omamo, Steven Were; D'Ieteren, G.D.M.; Iraqi, F.A. (Wiley, 2001)
This paper undertakes an ex ante economic analysis of research on how resistance to trypanosomosis - a dominant livestock disease in Africa - can be maintained and enhanced while retaining and reinforcing characteristics of economic importance to farmers, and on how 'trypanotolerance' can be imparted to susceptible animals while retaining their other important traits. The results indicate that potential benefits to research - historically field-based but increasingly biotechnology-driven - range from two to nine times potential costs and that the internal rate of return on investments can be six times the real interest rate. Field-based research, while exhibiting lower potential benefits on aggregate than does biotechnology research, is also less costly and, because of its more immediate payback, has higher internal rates of return. Returns to biotechnology research hinge on close links with field-based research and on strategic but relatively small incremental human and capital investments. The results also suggest that further research is needed to consistently identify and track the impacts of alternative intellectual property rights (IPRs) options on the levels and distributions of biotechnology research benefits.